PEER AND SELF-ASSESSMENT AT ESP CLASSES: CASE STUDY - Yuliana Lavrysh (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
In order to develop the skills and competences required in a professional environment, university students have to reflect on their own role in the learning process. The traditional methods of assessment do not assess reflective thinking, critical thinking, self-evaluation and peer evaluation. The following paper outlines and evaluates the implementation of peer and self-assessment techniques in higher education, in ESP course at National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute" as a case study. The rationale of the alternative type assessment systems is examined, and the efficiency of these methods is evaluated and compared by the use of attitudinal questionnaires completed by the participating students and the lecturer's assessments and feedback. The methodology to investigate the effect of peer and self-assessment as a part of the learning process includes literature observation, case study, developing marking criteria, examples of peer and self- assessment strategies and activities in ESP course. Forty quantitative peer and self-assessment studies were subjected to analysis. The study pointed to differences between self and peer assessments. Peer assessment was found to resemble more closely teacher assessments whereas self-assessment demonstrated difference with teacher's marks. One of the most essential conditions for objective and relevant performance of the evaluation was found as well-understood assessment criteria. Hypotheses concerning the greater validity of peer and self- assessments were not supported. We have drawn the conclusions that the application of peer and self- assessment methods improves students' critical thinking skills, involves students into learning and assessment processes, keeps motivation up to study and provides them with a greater ownership of the whole learning and assessment process. Therefore peer and self-assessment techniques could be effectively implemented in the course of ESP at universities.